FORMATION OF MODERN MANAGEMENT MECHANISMS IN THE FIELD OF TOURISM UNDER TRANSFORMATION CONDITIONS (Marketing Journal, 2025)
In this article, a comprehensive analysis of the issues of formation of modern management mechanisms in the field of Tourism of Uzbekistan in the context of 567 transformation processes is carried out. In recent years, the country has undergone extensive reforms aimed at developing tourism as a strategic sector of the economy. On the basis of statistics for the period 2020 -2024, indicators such as tourist flow, export receipts and the share of tourism in GDP were analyzed. In the field of Tourism, proposals have been developed for effective management mechanisms — digital technologies, state -owned partnerships, formation on the basis of human capital and territoria l development, modern management models, integrated digital platforms, the formation of modern management mechanisms in the field of Tourism.
Keywords: tourism management; transformation process; digital technology; public -private partnership; tourism policy; human capital; tourist infrastructure; strategic marketing; innovation in Tourism; Regional Development; Sustainable Tourism; tourism services expor t; tourist flow